2015
DOI: 10.1016/j.rppnen.2014.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative surgical complications after lung transplantation

Abstract: This is a review article on the main postoperative complications after lung transplantation: airways complications, vascular complications, pleural complications, surgical wound complications, and abdominal complications. Incidence data, severity, and major management regimens are reported. Postoperative complications after lung transplantation result in a significantly increased morbidity and mortality, with early diagnosis and therapy being extremely important.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…These improvements have decreased the main immediate complications of lung transplantation, especially extra-thoracic complications, of which gastrointestinal complications are of particular interest given their potential need for immediate surgical intervention [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These improvements have decreased the main immediate complications of lung transplantation, especially extra-thoracic complications, of which gastrointestinal complications are of particular interest given their potential need for immediate surgical intervention [2].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that gastrointestinal complications are frequent in patients who have undergone lung transplantation and are an important source of postoperative morbidity and mortality. There are also reports that these complications may have an independent impact on patient survival [2–7]. Among them, early-onset (< 30 days) and severe complications have been associated with high mortality rates after lung transplantation [8, 9].…”
Section: Introductionmentioning
confidence: 99%
“…This correlation with peristalsis might be related to the degree of vagal nerve manipulation during LT surgery. 43 - 46 As the vagal nerve controls primary and secondary esophageal peristalsis, reduced vagal tone affects esophageal contraction amplitude and prolongs bolus clearance. 6 , 47 , 48 On the other hand, using a parasympathomimetic agent, bethanechol was shown to empower vagal innervation and improve peristalsis and bolus transit time in patients with severe ineffective esophageal motility.…”
Section: Discussionmentioning
confidence: 99%
“…Pleural space complications, including empyema, pleural effusion, pneumothorax, and chylothorax, require treatment in approximately 22% of cases [ 20 ]. Pneumothorax is a source of air leaks in the parenchyma of the lung except for bronchial anastomosis complications, and it can occur when the donor/recipient size mismatch is severe [ 21 ]. Most of these complications can be resolved by maintaining and managing the chest tube; however, bronchial complications must be distinguished.…”
Section: Pleural Space Complicationsmentioning
confidence: 99%